1993
DOI: 10.2307/2719468
|View full text |Cite
|
Sign up to set email alerts
|

A Profile of The Manchu Language in Ch'ing History

Abstract: Each copy of any part of a JSTOR transmission must contain the same copyright notice that appears on the screen or printed page of such transmission. JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…Although Bartlett in an earlier article talked about the quantity and "importance" of the Grand Council archive in Manchu, I judge from the archival category-names listed in her article that they are wide-ranging but probably of rather minor importance as compared to the entire series in Chinese (Bartlett 1985). Similarly, other types of increasingly available Manchu-language sources are not quite of the nature and quality that Rawski would have us believe (Rawski 1996, 835;Crossley and Rawski 1993). The judgment of the late Joseph Fletcher, who formed a Manchu class of seven students at Harvard in the fall of 1981, merits our attention:…”
Section: A False Dichotomy: Rawski's Distortion Of My Thesismentioning
confidence: 95%
“…Although Bartlett in an earlier article talked about the quantity and "importance" of the Grand Council archive in Manchu, I judge from the archival category-names listed in her article that they are wide-ranging but probably of rather minor importance as compared to the entire series in Chinese (Bartlett 1985). Similarly, other types of increasingly available Manchu-language sources are not quite of the nature and quality that Rawski would have us believe (Rawski 1996, 835;Crossley and Rawski 1993). The judgment of the late Joseph Fletcher, who formed a Manchu class of seven students at Harvard in the fall of 1981, merits our attention:…”
Section: A False Dichotomy: Rawski's Distortion Of My Thesismentioning
confidence: 95%
“…Historians such as Beatrice Bartlett found that ‘Manchu did not substantially decline during the nineteenth century’ and even had advantages over Chinese in some aspects, such as frontier affairs, based on the study on Grand Council inventories. In Pamela Kyle Crossley and Evelyn Rawski's study of the history of the Manchu language, they noticed that bannermen, civilian literati, and westerners contributed to maintaining Manchu in the nineteenth century, which remained fundamental to research on the late Qing history…”
Section: The Polyglot Reality In the Late Qing Empirementioning
confidence: 99%
“…As Di Cosmo explained, the ritual Manchu language was ‘a tool more of rulership than of daily life’ among bannermen at court and throughout the empire. Edward Rhoads and Crossley further contextualized Manchu distinctiveness in the late Qing reform and revolution. Crossley used a three‐generation biography of a Manchu family to illustrate the ongoing ethnic conflicts in late imperial China Rhoads.…”
Section: Multilingualism and The Integrity Of The Qing Empirementioning
confidence: 99%
See 2 more Smart Citations